Diversity of non-tuberculous mycobacteria in heater-cooler devices: results from prospective surveillance. Issue 3 (July 2020) - Kaelin, M.B.; Kuster, S.P.; Hasse, B.; Schulthess, B.; Imkamp, F.; Halbe, M.; Sander, P.; Sax, H.; Schreiber, P.W.
SUMMARY: Objective: The international outbreak of cardiac-surgery-associated Mycobacterium chimaera infections was traced back to infectious aerosols originating from contaminated water reservoirs of heater-cooler devices (HCDs). In general, non-tuberculous mycobacteria (NTM) frequently colonize water systems and can contaminate medical devices. Data on detection of NTM other than M. chimaera in samples gathered from HCDs are scarce. The present study summarizes prospective mycobacterial surveillance of five HCDs over more than 4 years. Methods: Five LivaNova 3T (London, UK) HCDs, acquired factory-new in 2014, were followed prospectively. Until mid-April 2014, the HCDs were maintained according to the manufacturer's recommendations, and subsequently, they were maintained according to an intensified in-house protocol including exhaust air evacuation. Mycobacterial surveillance cultures consisted of monthly water samples gathered from patient and cardioplegia circuits, as well as airflow samples. Results: Of 441 water samples, 170 (38.6%) revealed NTM growth. The most frequently detected NTM were M. chimaera [ N =120 (67.4%)], Mycobacterium gordonae [ N =35 (19.7 %)] and Mycobacterium paragordonae [ N =17 (9.6%)]. Growth of NTM, M. chimaera and M. paragordonae was significantly more common in water samples derived from the patient circuit than the cardioplegia circuit of the HCD. Three (2.0%) of 150 air samples grew NTM. Conclusion: Growth of NTM in HCD water samples was common. Diverse NTM species were detected, with M. chimaera being the most common. The majority of air samples remained negative. The relevance of NTM other than M. chimaera contaminating HCDs is poorly defined, but a recent report on an HCD-associated outbreak with Mycobacterium abscessus confirmed a potential threat.